Rabelais's radical farce: late medieval comic theater and its function in Rabelais - Hayes, E. Bruce (Ashgate, 2010)
Introduction -- Part I: the world of farce: the ethics and ethos of farce; tant de langaige: the languages of farce -- Part II: Rabelais's radical farce: humanist satirical farce in Pantagruel and Gargantua; unresolved farces and "tragicques farce": Tiers and Quart livres -- Conclusion